Pharmacological observations on the hypotensive action of extracts of teleost fish urophyses (urotensin I) in the rat - Lederis, K. (1974)
1 Intravenous injections of urotensin I regularly caused a long-lasting, dose-related, lowering of blood pressure and an increase in heart rate in conscious rats, or a reduction in perfusion pressure in the isolated hind limb of the rat. 2 After subcutaneous administration, the hypotensive effect of urotensin I was greater in extent and in duration (> 24 hours). 3 Anaesthesia with ether, chloralose, pentobarbitone and thiobarbitone caused a decrease in blood pressure and only slightly diminished the hypotensive effect of urotensin. 4 Mecamylamine, hexamethonium, atropine, phenoxybenzamine, propranolol and diphenhydramine did not alter the effect of urotensin in conscious rats or in the isolated hind limb, although the effects of the respective agonists, i.e. nicotine, acetylcholine, noradrenaline, isoprenaline and histamine were inhibited. 5 In conscious rats, pressor effects of adrenaline, noradrenaline, nicotine and angiotensin II, and depressor effects of acetylcholine and bradykinin, were decreased or inhibited, whereas the hypotensive effect of phenoxybenzamine was potentiated by previous administration of urotensin I. Carotid occlusion reflex was partially inhibited by lower doses of urotensin and abolished by higher doses in rats lightly anaesthetized with chloralose. Urotensin elicited postural hypotension in rats anaesthetized with pentobarbitone. 6 The increase in heart rate produced by urotensin was not affected by phenoxybenzamine, but was abolished by propranolol or ganglion blocking agents (mecamylamine or hexamethonium). 7 It is concluded that urotensin elicits hypotension in the rat by a direct dilatory action on the resistance vessels causing a simultaneous reflex tachycardia.